Irresistible Signs : The Genius of Language and Italina National Identity - Gambarota, Paola (Book collections on Project MUSE., 2011)
"Language is now understood as a key component of cultural identity, but discourses on linguistic nationalism are only a few centuries old. In Irresistible Signs, Paola Gambarota investigates the connection between Italian language and national identity over four hundred years, from late-Renaissance linguistic theories to nineteenth-century nationalist myths. Challenging the consensus that linguistic nationalism originated with nineteenth century German philosophers, Irresistible Signs advances a more nuanced theory of how culture and language become inextricably linked through literary and rhetorical elements. Gambarota combines Anglo-American theories of the nation with the most advanced Italian scholarship on language ideology and delves into ideas from Giambattista Vico, Giacomo Leopardi, and Melchiorre Cesarotti. Irresistible Signs also explores how images of national communities are represented within vernaculars, affirming their influence in shaping contemporary models of monolingual nationhood."--Pub. desc.